Adjudicating Waqf Disputes: Islamic Legal Doctrine in Court Practice - Maryani, Maryani; Zulkarnaen, Zulkarnaen; Sitompul, Osli G.; Uldin, Beni; Hendriek, Hendriek (Decisio: Journal of Judicial Law and Procedure, 2026)
Court decisions in waqf disputes constitute a strategic arena for the formation of Islamic law in practice, where classical fiqh doctrines interact dynamically with state law. This article examines judicial reasoning in waqf disputes adjudicated by Indonesian Religious Courts, focusing on how judges integrate Islamic legal doctrines with positive law to ensure legal certainty and protect public interests. Employing a socio-juridical legal research approach based on court decisions, this study analyzes selected waqf rulings using legal reasoning analysis. Several landmark cases, including decisions from the Religious Courts of Jakarta Selatan and Kediri, are examined to capture variations in judicial argumentation. The findings demonstrate that judges do not merely apply waqf regulations textually, but actively construct legal meaning through contextual interpretation. Classical fiqh principles such as taʿbīd, luzūm, and the social function of waqf are consistently invoked, yet rearticulated within the framework of Law Number 41 of 2004 on Waqf. Judicial reasoning reflects a pattern of integrative ijtihād, in which fiqh doctrines provide substantive legitimacy, while positive law ensures procedural structure and legal certainty. Judicial discretion is also exercised to balance formal legal proof with the social realities of waqf practices. This study concludes that judicial reasoning plays a decisive role in shaping contemporary waqf law as a living law. By positioning court decisions as a key site of legal development, this article contributes to Islamic legal studies, judicial studies, and waqf governance discourse, while offering normative insights for strengthening judicial argumentation and safeguarding waqf as a public institution.